New reactive poly(ionic liquid)s synthesized by polymer analogous conversion of maleic anhydride containing polymers. (25th July 2016) - Suckow, Marcus; Zschoche, Stephan; Heinrich, Gert; Voit, Brigitte; Böhme, Frank
Abstract: New poly(ionic liquids) were synthesized by a two stage polymer analogous reaction. In the first stage, the reactive maleic anhydride groups of the starting polymer were converted with 1-(3-aminopropyl)-imidazole. The second stage comprises an alkylation reaction of the imidazole groups with various alkylbromides. This approach allowed tailoring of the polymer properties to a large extent. With the degree of conversion, the number of reactive groups remaining in the polymer could be adjusted. The possibility to preserve reactive groups opens new applications of the poly(ionic liquid)s as reactive blend components. As an example, reactive mixtures with bromobutyl rubber were prepared which exhibited pronounced self-healing properties. Graphical abstract: Highlights: New poly(ionic liquid)s with reactive groups were synthesized. The polymers were prepared by polymer analogous conversion in solution. The number of reactive groups could be tailored by the degree of conversion. Solubility and thermal behavior of the poly(ionic liquid)s were tailored. Mixtures of the poly(ionic liquid)s and bromobutyl rubber exhibited self-healing.